2018
DOI: 10.1002/jsfa.8824
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, stability and bioavailability of astaxanthin succinate diester

Abstract: The thermal stability and bioavailability of ASD were higher than that of the non-esterified free AST and common free AST, respectively. Additionally, AST accumulation in different tissues of the ASD group was multifold higher than that of free AST. These results prove that ASD may serve as a better source of AST for human nutrition than does free AST. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 39 publications
5
27
1
Order By: Relevance
“…Therefore, in nature, it is either conjugated with proteins or esterified with one or two fatty acids (monoester or diester) to be more stable [11]. AST esters are better absorbed in the small intestine than AST, have higher bioavailability, and accumulate more in various tissues [12][13][14]. Fukami et al synthesized astaxanthin n-octanoic acid esters, a type of medium-chain fatty acid esters, through chemical and enzymatic methods [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in nature, it is either conjugated with proteins or esterified with one or two fatty acids (monoester or diester) to be more stable [11]. AST esters are better absorbed in the small intestine than AST, have higher bioavailability, and accumulate more in various tissues [12][13][14]. Fukami et al synthesized astaxanthin n-octanoic acid esters, a type of medium-chain fatty acid esters, through chemical and enzymatic methods [10,15].…”
Section: Introductionmentioning
confidence: 99%
“…okada et al (38) showed that the metabolism of aST in a group of smokers was faster compared with the non-smokers group, which may be attributed to the antioxidant effect of aST. a previous study found that dietary oils may enhance the absorption of aST bioavailability in humans (39). in addition, Mercke et al (40) determined the bioavailability of aST from H. pluvialis dispersed in synthetic hydrophilic surfactant polysorbate 80 (B), which is a lipid-based formulation, was 1.7-3.7 times higher compared with the commercial formulation.…”
Section: Discussionmentioning
confidence: 98%
“…Bioavailability of astaxanthin can be enhanced by the formation of an ester by conjugating it with succinic anhydride. Astaxanthin succinate diester is more thermally stable and bioavailable to the body tissues than ree astaxanthin (Qiao et al, 2018).…”
Section: B I O -Avail Ab Ilit Y and Source S Of A S Ta X Anthinmentioning
confidence: 98%